Teacher training in mathematics: influence in Aida’s professional development - Martins, Cristina (2010)
This study has as its main goal to study teacher’s Professional development through participation in the Training program in Mathematics for Primary School Teachers. This training program is underway in Portugal since the academic year of 2005/2006. It foresees undertaking three kinds of sessions (i) group training sessions for the development of curricular proposals to be tried out in the classroom, and the deepening of mathematical knowledge; (ii) classroom supervision sessions putting in practice the planning sorted out during training sessions, and (iii) a plenary session at the end of the program to assess the work carried out. Evaluation is based on portfolio building. We aim at providing an answer to the following research questions: - How does a teacher’s professional knowledge evolve throughout training? In particular, mathematic and didactic knowledge? - What changes can one see in the teachers’ teaching practices throughout training? How does the teacher identify and justify them? - How does the teacher’s reflecting ability evolve throughout training? - What is the contribution of portfolio usage to the teacher’s professional knowledge? Mathematic research during the last decade has shown that a solid knowledge is needed to teach well (Ma, 1999). Even teaching elementary math demands both an extensive mathematical knowledge and a wide range of pedagogical abilities. Professional knowledge is action-directed knowledge, constructed and developed during experience and reflection upon experience (Santos, 2000). Elbaz (1983) stresses the fundamentally practical nature of teachers’ professional knowledge, built upon theoretical knowledge and knowledge arising from experience. Schön’s (1983) contribution, having as a starting point the disagreement with the methods and epistemological assumptions of technical rationality, has also tried to understand how Professional learn in practice, characterizing Professional knowledge as knowledge in action. Shulman (1986) stresses the importance of content didactic knowledge, knowledge which goes beyond content per se into the dimension of content knowledge to teach. Ball, Thames, Phelps (2008), based on Shulman, consider that content knowledge is formed by horizon knowledge, common content knowledge and by specialized content knowledge. Pedagogical content knowledge is formed by knowledge of content and teaching, knowledge of content and students and knowledge of content and curriculum. Several authors have devoted themselves to studying strategies for the teacher’s Professional knowledge, for instances reflection (Schön, 1983), colaborative work, (Day, 2001) and participation in actions and projects (Hiebert, Gallimore & Stigler, 2002). The portfolio also helps assessment to assume an essentially regulating function (Santos, 2004), promoting the teachers professional development (Lyons, 1999). In this poster we hope to present the data concerning the professional develop of a teacher participating in this research – teacher Aida.